2013
DOI: 10.1002/9780470559277.ch120267
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Control of Gene Expression in Mammalian Cells and in Mice Using the LightOn System

Abstract: A light‐switchable transgene system could be a powerful optogenetic tool for the precise manipulation of spatiotemporal gene expression in multicellular organisms. We have developed the LightOn system, which consists of a single chimeric protein (GAVPO) that can homodimerize and bind to promoters upon exposure to blue light, activating transcription of a target gene. This article describes protocols for precise control of gene expression in mammalian cells and mice using the LightOn system. These protocols can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 54 publications
(115 reference statements)
0
23
0
1
Order By: Relevance
“…Optimization and characterization of TAEL, an optogenetic gene expression system for zebrafish Two LOV-based optogenetic expression systems, LightOn and EL222, were recently developed (Wang et al, 2012;Chen et al, 2013;Motta-Mena et al, 2014). We previously showed that the EL222 system could function in zebrafish embryos (Motta-Mena et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Optimization and characterization of TAEL, an optogenetic gene expression system for zebrafish Two LOV-based optogenetic expression systems, LightOn and EL222, were recently developed (Wang et al, 2012;Chen et al, 2013;Motta-Mena et al, 2014). We previously showed that the EL222 system could function in zebrafish embryos (Motta-Mena et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The LightOn system is based on a synthetically constructed transcriptional activator, GAVPO, consisting of the LOV domain from the Neurospora protein Vivid fused to both a Gal4 DNA-binding domain and a p65 transactivating domain. Upon light-induced dimerization, GAVPO binds to its corresponding UAS promoter and induces transcription of a gene of interest (Wang et al, 2012;Chen et al, 2013). The EL222 system relies on similar principles but is based on a naturally occurring light-responsive transcription factor, EL222, found in Erythrobacter litoralis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we tested whether the ability to spatially focus activation can improve the method. Stimulation of optogenetic tools is often realized using custom-built hardware and continuous illumination [15][16][17] . However, microplate readers commonly part of screening platforms employ discontinuous flash lamps.…”
mentioning
confidence: 99%